Calpain-2 expression is associated with response to platinum based chemotherapy, progression-free and overall survival in ovarian cancer - Storr, Sarah J.; Safuan, Sabreena; Woolston, Caroline M.; Abdel-Fatah, Tarek; Deen, Suha; Chan, Stephen Y.; Martin, Stewart G. (Wiley, 2012)
Ovarian cancer is routinely treated with surgery and platinum-based chemotherapy. Resistance is a major obstacle in the efficacy of this chemotherapy regimen and the ability to identify those patients at risk of developing resistance is of considerable clinical importance. The expression of calpain-1, calpain-2 and calpastatin were determined using standard immunohistochemistry on a tissue microarray of 154 primary ovarian carcinomas from patients subsequently treated with platinum-based adjuvant chemotherapy. High levels of calpain-2 expression was significantly associated with platinum resistant tumours (P = 0.031). Furthermore, high expression of calpain-2 was significantly associated with progression-free (P = 0.049) and overall survival (P = 0.006) in this cohort. The association between calpain-2 expression and overall survival remained significant in multivariate analysis accounting for tumour grade, stage, optimal debulking and platinum sensitivity (hazard ratio = 2.174; 95% confidence interval = 1.144–4.130; P = 0.018). The results suggest that determining calpain-2 expression in ovarian carcinomas may allow prognostic stratification of patients treated with surgery and platinum-based chemotherapy. The findings of this study warrant validation in a larger clinical cohort.